PAHAM KENABIAN DALAM TASAWUF FALSAFI IBN 'ARABI DAN RELEVANSINYA TERHADAP PAHAM KEAGAMAAN - HAJAM HAJAM (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2014)
In the books of the view that prophecy is considered final, prophetic door was closed, prophecy is God's choice without the intervention of the human mind and human living must believe. This opini shows that the understanding of religious texts (Al Qur'an and Hadis) by not playing with textual understanding will result in a universal understanding and holistic, as prophetic discourse. But in the books stating that the prophecy does not just stop at the region shariah doctrine, but the prophecy is still going on to lead every race religion and culture. To dissect this research study can be used approach is to use a hermeneutic approach as a method of contextual interpretation is patterned.